An update on diagnostic imaging studies for viral encephalitis. (September 2012) - Kawamura, Naoki; Kizawa, Madoka; Ueda, Akihiro; Niimi, Yoshiki; Mutoh, Tatsuro
Viral encephalitis is still a life-threatening disease occurring at any age. It is critical to make a rapid and correct diagnosis for a better outcome of the disease. Accumulating evidence has suggested that MRI is a powerful tool for the detection of any lesion of the CNS caused by viral infections and helps to initiate the timely treatment. In this review, we summarize the current understanding of MRI findings of viral encephalitis, especially related to HSV, HIV, varicella zoster, Japanese encephalitis, John Cunningham, and influenza viruses. With these considerations, we learnt that the inclusion of diffusion-weighted image sequences on routine MRI examination would have a significant value in detecting the pathologic changes that occur following viral invasion of the CNS.